Institute of Metals Division - Habit Plane of Hydride Precipitation in Zirconium and Zirconium-Uranium - F. W. Kunz; A. E. Bibb (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1961)
A platelet form of zirconium hydride was found in zirconium and ZY-1 wt pct U single crystals containing hydvogen in the range of 50 to 100 ppm. The habit planes for the hydride plateletg in the zirconium crystals were found to be {1012}, {1121}, and (1122) while the habit planes in the ZY-1 wt pct U crystals were {1121), {1123}, and (1.231). With the exception of the {1231} plane, these have been identified as the twin planes in zirconium. The different effect of hydridc on the mechanical puoperlies of zirconium at high and low strain rates has been explained in terms of the defornzation mechanism and the habit planes of the hydride. ZIRCONIUM and zirconium-base alloys are considered for many nuclear reactor applications, where the pick-up of hydrogen is a distinct possibility, if not an unavoidable occurrence. An excellent example of this is the absorption of hydrogen by zirconium and its alloys during aqueous corrosion, where as much as 30 pct of the hydrogen produced by the corrosion reaction is picked up by the metal. Under the proper conditions, the absorbed hydrogen would precipitate as zirconium hydride and consequently alter the mechanical and physical properties of the zirconium-base alloys. The knowledge obtained from a study of the crystallographic aspects of the hydride precipitation is necessary for the interpretation of the observed changes in the mechanical and physical properties. The deleterious effect of hydrogen on zirconium-base materials is not always observed in normal slow tensile loadings at or above room temperature, but becomes immediately obvious under impact loading, where the energy absorbed decreases with increasing hydrogen content,' and in notched specimens where triaxial loadings are attained.2 This effect is of serious consequence in the applications of Zr where shock loads or high strain rates are experienced. The purpose of this investigation was to determine the crystallographic planes of the Zr and Zr-1 wt pct U matrices upon which zirconium hydride will precipitate and to correlate these with the observed mechanical property data. PROCEDURE Crystal Growth—Single crystals of Zr and Zr-1 wt pct U alloy were used in this investigation. The Zr crystals were made from sponge that had a typical analysis as shown in Table I. Large grains were grown in this material by rapid cooling an arc-melted charge in a button furnace. This operation undoubtedly lowered the volatile impurity concentration below those listed in Table I. Back-reflection Laue patterns of these large grains showed the presence of considerable substructure and lattice distortion within each grain. It was found that an 18-day anneal in an argon atmosphere at 840°C (a high a heat-treatment) followed by furnace cooling, resulted in the further growth of the large grains and removed the detectable substructure ana lattice distortion. Equiaxed crystals with a cube edge of approximately 1/4 in. were produced in this manner. Large crystals of Zircaloy-2 (1.5 wt pct Sn, 0.15 wt pct Fe, 0.1 wt pct Cr, 0.05 wt pct Ni) also were produced by this technique but the large amount of substructure formed could not be removed by annealing. The Zr-1 wt pct U solid solution crystals were produced from an alloy rod consisting of Westing-house-Foote hafnium-free crystal bar zirconium and depleted uranium. The chemical analysis of the alloy is also given in Table I. Three-inch sections were cut from an 0.120-in.-diameter alloy rod and tapered to a fine point on each end. The samples were sealed in evacuated Vycor tubes, homogenized for 5 hr at 1000°C in the ß-phase field, and slowly lowered in a gradient furnace into the a phase (800°C), annealed for 60 hr at this temperature to produce grain growth and furnace cooled. This technique produced large grains approximately 1/2 to 3/4 in. long over the entire cross section of the rod, which were free of observable substructure. Metallographic examination up to X1000 did not show the existence of any second phase in these grains. Crystal Orientation—All crystals were abraded on fine emery paper to produce two flat surfaces 90 deg to each other. The crystals were analyzed by the standard Back-Reflection Laue technique to obtain the crystal orientation with respect to the abraded surfaces. The Back-Reflection Laue Photograms of all crystals used were clear and sharp indicating that the crystals were free from any substructure that could be detected by these means. Hydriding—Only samples containing four to five grains were used for hydriding. Samples that exhibited fine grained patches were discarded. The samples were hydrided using the following technique. After etching in 48 vol. pct HNO3, 48 vol. pct H2O, and 4 vol. pct HF (48 pct) solution, the specimens